IMPLEMENTASI LAYANAN POLISI 110 TERHADAP KECELAKAAN LALU LINTAS OLEH BIRO OPERASI POLDA BALI DI KOTA DENPASAR - Kusuma, I Made Mahawidya (Kerta Dyatmika, 2026)
Police Service 110 or formerly popular as Call Center110 is a form of Polri service to the public to report/complain about problems that occur related to Kamtibmas disturbances or criminal acts/violations faster for the implementation of maximum public security services. Based on this, problems can be formulated, namely: how is the implementation of the 110 police service by the Bali Police operations bureau in Denpasar city in handling traffic accident cases and what are the factors that hinder the handling of traffic accident cases through the 110 police service by the Bali Police Operations Bureau in Denpasar city. The type of research used is empirical juridical research, descriptive, using primary data and secondary data, data collection techniques in empirical legal research, namely document studies, interviews and observations. Data is processed and analyzed with qualitative techniques according to the nature of the data then presented descriptively, then analyzed qualitatively. The results of this study are the implementation of police service 110 by the Bali Police operations bureau in the city of Denpasar in handling traffic accident cases are: the operator opens the Police Service Agent Application 110; receive Reports/Complaints while verifying caller's identity and location; record Reports/Complaints; forward the Report/Complaint to the nearest police ranks; monitor follow-up from the ranks of the police/related function units and officers in the field; receive progress reports; inform the status of the Report; Record a series of follow-up Reports/Complaints; and provide responses to the whistleblower. The inhibiting factors of handling traffic accidents through the 110 police service are internal factors and external factors.